Growth and Yield of Lentil as Influenced by Zinc and Boron Management (Bangladesh Agronomy Journal, 2024)
A field experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh, during the period from November 2021 to March 2022 to evaluate the influence of micronutrients management on growth and yield of two lentil varieties viz., BARI Masur-8 (V1) and Binamasur-8 (V2) and 6 micronutrients management (no fertilizer - F1, recommended fertilizer dose (RFD) (40-90-40-55 Kg ha−1 of urea-TSP-MoP-Gypsum) with 10 Kg ha−1 ZnSO4 as basal - F2, RFD with zinc (Zn) as foliar spray - F3, RFD with Zn and boron (B) as foliar spray - F4, 50% RFD + 50% cow dung (5 t ha−1) - F5 and 50% RFD + 50% cow dung + Zn and B as foliar spray - F6). No significant effect had found for variety except 1000-seed weight but micronutrients management along with interactions significantly effects on all studied parameters of lentil. The higher 1000-seed weight (34.16 g) was recorded in BARI Masur-8. The highest plant height (37.09 cm), number of branches plant−1 (7), dry weight of root plant−1 (159.17 mg), dry weight of shoot plant−1 (3319.33 mg) and number of pods plant−1 (62) was observed at F6 treatment. The highest 1000-seed weight (31.68 g) were recorded at F2 treatment. The highest weight of nodules plant−1 (10.33 mg at 60 DAS), seed yield (2.62 t ha−1), straw yield (2.12 t ha−1) and biological yield (4.74 t ha−1) were found at F3 treatment. The highest plant height (38.45 cm), number of branches plant−1 (7), number of pods plant−1 (63), seed yield (2.91 t ha−1) and harvest index (58.65%) were recorded at V2F6 whereas the highest weight of nodules plant-1 (26 mg), straw yield (2.22 t ha−1) and biological yield (5.02 t ha−1) were found at V1F3 but the highest 1000-seed weight (34.87 g) at V1F1. The highest number of seeds pod−1 (1.83) was found at V2F1. So, two varieties showed similar performance on yield. Foliar application of Zn has the potentiality to increase seed yield. The variety Binamasur-8 with 50% RFD + 50% cow dung + Zn and B (F6) as foliar spray could bring maximum yield (2.91 t ha−1) of lentil followed by treatment F2, F3, and F4.Bangladesh Agron. J. 2024, 26(2): 34-40